Design and manufacturing workflow of a patient specific 3-dimensionally engineered tracheo-bronchial stent (Transactions on Additive Manufacturing Meets Medicine, 2021)
Collapsing airway pathologies, such as vanishing bronchus syndrome, are routinely treated by airway stent implantation. Off-the-shelf stents are appropriate for the treatment of most patients. However, in some cases, these commercially available stents do not fit the patient's airway anatomy sufficient, resulting in a high risk for dislocation and infection. In this article, we present a process for design and manufacturing of patient-specific tracheobronchial stents that allows treatment of patients in whom standard treatment is not appropriate.
Keywords: patient specific; tracheo-bronchial stent; additive manufacturing; manufacturing workflow